Pereskia aculeata Miller Flour: Metabolic Effects and Composition - Barbalho, Sandra Maria; Guiguer, Élen Landgraf; Marinelli, Paulo Sérgio; Do Santos Bueno, Patrícia Cincotto; Pescinini-Salzedas, Leticia Maria; Dos Santos, Mirele Cristine Batista; Oshiiwa, Marie; Mendes, Claudemir Gregório; De Menezes, Manoel Lima [UNESP]; Nicolau, Cláudia Cristina Teixeira; Otoboni, Alda Maria; De Alvares Goulart, Ricardo (SAGE Publications, 2016)
Pereskia aculeata Miller is known in Brazil as ora-pro-nobis (OPN) and has been used commonly in the folklore medicine. The purpose of our study was to evaluate the composition and the effects of OPN flour on the metabolic profile and intestinal motility of Wistar rats. Animals were divided randomly into five groups (n = 10): G1 (control group) and G2 (treated with OPN flour). For the intestinal motility: G3 (control group), G4 (treated with senne), and G5 (treated with OPN flour). After 40 days, G1 and G2 were euthanized and metabolic profiles were analyzed (glycemia, cholesterol, triglycerides, high density lipoprotein [HDL-c], C reactive protein, AST, ALT, Lee Index, weight, and visceral fat). The flour of OPN was effective in reducing percentage of weight gain, visceral fat, levels of total cholesterol, triglycerides, low density lipoprotein, very low density lipoprotein, and increased HDL-c. Significance was also found in the distance covered by the activated charcoal from the pylorus to the beginning of the cecum, which was higher in animals treated with OPN. Our results indicate that OPN flour may bring health benefits, as the improvement of the intestinal motility, and it is associated with reduction of visceral fat and lipid profile, as well as the increase of HDL-c levels. With these results, we may suggest that the incorporation of this flour in different industrial products may be a convenient and effective way for the intake of healthier products.
Keywords: Cholesterol; Glycemia; Intestinal motility; Pereskia aculeata; Visceral fat; Wistar rats